Morphometric changes in rat periwound skin during healing of excisional wounds after exposure to chronic social stress - Makyeyeva, L. V.; Frolov, O. K.; Aliyeva, O. G.; Макєєва, Людмила Валеріївна; Фролов, О. К.; Алієва, Олена Геннадіївна (My University, 2025)
Background. Chronic stress is the most common systemic factor that negatively affects the body's overall resistance, including wound healing. While many aspects of skin recovery after a surgical wound are well defined, the involvement of cells in the periwound rarea emains unsufficiently studied. Objective. To determine the morphological features of the periwound skin at different stages of the healing process after exposure to chronic social stress. Methods. Chronic social stress was modeled through long-term psychoemotional exposure in Wistar laboratory rats of the experimental group. Animals in both control and experimental groups were wounded in the interscapular area by skin excision. The material of the periwounds was collected on the 1st, 3rd, 7th, 14th and 30th days of wound healing and processed according to standard histological methods. Results. Exposure to chronic social stress led to thinning of the skin layers even before wounding. Visual wound healing was delayed. The main reparative processes by phases (inflammation, proliferation, and remodulation) also occurred with significant delays. Conclusions. Aggressive-dominant social stress is a rather strong damaging factor for susceptible animals, leading to impaired physiological skin regeneration. This was evident in the thinning of skin layers observed in histological samples even before wound application, resulting from reduced proliferation and differentiation processes. The negative consequences of chronic social stress were further manifested in the healing of a surgical wound: the repair processes during the main phases, in particular inflammation and proliferation, were delayed, which ultimately led to the chronicity of reparative regeneration. Проблематика. Хронічний стрес є найбільш поширеним системним фактором, який негативно впливає на загальну резистентність організму, в т.ч. і на загоєння ран. Добре визначені низка аспектів відновлення шкіри після нанесення хірургічної рани, однак залученість клітин крайової ділянки ран вивчена не достатньо. Мета. Визначити морфологічні особливості крайової ділянки ран шкіри на різних етапах процесу загоєння після впливу хронічного соціального стресу. Методика реалізації. Моделювали хронічний соціальний стрес шляхом тривалого пcихоемоційного впливу на лабораторних щурів лінії Wistar експериментальної групи. Тваринам контрольної та експериментальної груп наносили різану рану в міжлопатковій ділянці. Забирали матеріал крайової ділянки ран на 1, 3, 7 ,14 та 30-й дні загоєння ран і обробляли за стандартною гістологічною методикою. Результати. Перенесений хронічний соціальний стрес ще до нанесення рани призводить до потоншення шарів шкіри. Візуальне загоєння рани йшло з великим запізненням. З достовірною затримкою відбувалися й основні репаративні процеси за фазами: запалення, проліферація, ремодуляція. Висновки. Агресивно-домінантний соціальний стрес є досить сильним ушкоджуючим фактором для сприйнятливих тварин, що призводить до порушення фізіологічної регенерації в шкірі, яке виражалось у витонченні шарів у гістологічних зразках шкіри, ще до нанесення рани за рахунок зниження процесів проліферації та диференціації. Негативні наслідки хронічного соціального стресу далі виявлялися і в загоєнні хірургічної рани: затягувалися процеси репарації на основних фазах, зокрема запаленні та проліферації, що зрештою призвело до хронізації репаративної регенерації.
Морфометричні зміни крайової зони ран шкіри щурів під час загоєння різаних ран після впливу хронічного соціального стресу
Keywords: wound healing; chronic social stress; periwound; epidermis; dermis; subcutaneous tissue; загоєння ран; хронічний соціальний стрес; крайова зона ран; епідерміс; дерма; підшкірна клітковина